Fighting eimeriosis by using the anti-eimerial and anti-apoptotic properties of rhatany root extract - Al-Quraishy, Saleh; Abdel-Gaber, Rewaida; Alamari, Ghada; Meryk, Andreas; El-Ashram, Saeed; Al-Shaebi, Esam M.; Dkhil, Mohamed A. (Frontiers in Immunology, 2024)
Over the last decade, extensive use of coccidiostats to treat and control Eimeria infection has developed drug resistance, prompting the search for new alternative therapies. Rhatany is proven to have various pharmacological properties. The present study aimed to in vitro and in vivo evaluate the effect of Rhatany roots extract (RRE) as an anti-eimerial and anti-apoptotic agent against murine eimeriosis. In vitro anti-eimerial activity of RRE, amprolium, phenol, DettolTM, and formalin were studied after incubation with non-sporulated Eimeria oocysts. For the in vivo study, twenty-five male C57BL/6 mice were randomly allocated into five groups. Animals in the first group were just given distilled H2O, while those in the second group were given RRE for 5 days. Eimeria parasite’s oocysts were infected into the third, fourth, and fifth groups. For treatment, RRE and amprolium were orally given to the 4th and 5th groups for five days, respectively. All mice were euthanized, on day 5 post-infection, to collect the jejunal tissues under study. Investigations were undertaken into the oocyst output in faeces and goblet cells in mice jejuna. Assays for GPx, H2O2, and MPO were also performed. In jejunal tissue, Caspase-3 was counted using immunohistochemistry, while Bax and BCL-2 were assayed using ELISA. mRNA expression of MUC2 was detected using real-time PCR. In vitro study revealed that RRE significantly inhabited the oocyst sporulation in a dose-dependent manner. By day 5 after infection, number of oocysts in mice faeces was significantly reduced after RRE treatment compared to the infected group. Eimeria infection reduced the number of goblet cells of mice jejuna and its specific gene, MUC2. Treatment increased the number of goblet cells/villus, associated with upregulation for MUC2. Also, the Eimeria experimental infection lowered the activity GPx, while increasing H2O2 as well as the activity of MPO. Production of apoptotic markers including Caspase-3 and Bax was significantly elevated while decreasing the anti-apoptotic marker of BCL2. Our study proved that RRE significantly reduced oxidative stress, and apoptotic markers as well as the inflammatory activity of MPO. Also, antioxidant enzyme and anti-apoptotic activity in the jejunum of E. papillata-infected mice were enhanced after RRE treatment.